Virtual rapport with expressions of gratitude in responding online reviews - Taw, Ly Wen; Paramasivam, Shamala; Libert, Alan; Moskovsky, Christo; Darmi, Ramiza; Jalaluddin, Ilyana (Universiti Putra Malaysia, 2022)
The development of web-based technologies has increased the popularity of an online type of word-of-mouth, known as electronic word-of-mouth (eWOM). With the proliferation of online platforms, online reviews as eWOM have significantly influenced consumers’ purchase decisions in various industries. Given that eWOM can be immensely influential in businesses, engaging in digital platforms is crucial in rapport building with customers. Responding to online reviews can have a positive impact on both customer relationships and online reputation management. Expressing gratitude can create rapport and build trust with customers as a sense of appreciation can be kindled. Building on Spencer-Oatey’s Rapport Management Model, this study examines expressing gratitude strategies in the hotel responses to positive online reviews on TripAdvisor. Using purposeful sampling, particularly intensity sampling, the hotel responses were collected from Malaysian five-, four- and three-star hotels, which are situated in popular tourist destinations. The study findings show that four-star hotels accounted for the highest frequency of expressing gratitude strategies, followed by five- and three-star hotels. The five- and four-star hotels tend to vary their expressing gratitude strategies. It was also found that there was a significant relationship between the hotel star rating categories, the strategies of gratitude expression and lexical choice in those strategies. This study will establish an understanding of digital rapport management strategies from a linguistic perspective.